Conserved cysteines in Mason-Pfizer monkey virus capsid protein are essential for infectious mature particle formation - Píchalová, Růžena; Füzik, Tibor; Vokatá, Barbora; Rumlová, Michaela; Llano, Manuel; Dostálková, Alžběta; Křížová, Ivana; Ruml, Tomáš; Ulbrich, Pavel (Virology, 2018)
Retrovirus assembly is driven mostly by Gag polyprotein oligomerization, which is mediated by inter and intra protein-protein interactions among its capsid (CA) domains. Mason-Pfizer monkey virus (M-PMV) CA contains three cysteines (C82, C193 and C213), where the latter two are highly conserved among most retroviruses. To determine the importance of these cysteines, we introduced mutations of these residues in both bacterial and proviral vectors and studied their impact on the M-PMV life cycle. These studies revealed that the presence of both conserved cysteines of M-PMV CA is necessary for both proper assembly and virus infectivity. Our findings suggest a crucial role of these cysteines in the formation of infectious mature particles.
Keywords: HEK293 Cells; buněčné linie; lidé; mutace; Cysteine mutagenesis; sestavení viru; HEK293 buňky; proviry; Cell Line; Virion; genetické vektory; Genetic Vectors; Humans; Capsid Proteins; virion; M-PMV capsid; Proviruses; Cysteine; Mutation; M-PMV infectivity; Virus Assembly; Virus core stability; virové plášťové proteiny; Retrovirus assembly; Masonův-Pfizerův opičí virus; cystein; Mason-Pfizer monkey virus